Neutron macromolecular crystallography with LADI-III - Blakeley, Matthew P. (2010)
At the Institut Laue-Langevin, a new neutron Laue diffractometer LADI-III has been fully operational since March 2007. LADI-III is dedicated to neutron macromolecular crystallography at medium to high resolution (2.5-1.5 Å) and is used to study key H atoms and water structure in macromolecular structures. An improved detector design and readout system has been incorporated so that a miniaturized reading head located inside the drum scans the image plate. From comparisons of neutron detection efficiency (DQE) with the original LADI-I instrument, the internal transfer of the image plates and readout system provides an approximately threefold gain in neutron detection. The improved performance of LADI-III, coupled with the use of perdeuterated biological samples, now allows the study of biological systems with crystal volumes of 0.1-0.2 mm3, as illustrated here by the recent studies of type III antifreeze protein (AFP; 7 kDa). As the major bottleneck for neutron macromolecular studies has been the large crystal volumes required, these recent developments have led to an expansion of the field, extending the size and the complexity of the systems that can be studied and reducing the data-collection times required.